Asylum spaces as spaces of nonrecognition: the ambiguities of welcoming and educating asylum-seeking children in Norway - Kalisha, Wills (Frontiers in Education, 2024)
Asylum has historically been a refuge for the persecuted. However, it now faces a fundamental antagonism between asylum and law, which often overlooks the rights of children seeking asylum. This paper explores the historical concept of asylum law from its inception in antiquity and the Roman era and its entanglements with the education of children. It also examines asylum’s relevance to current conflicts over the educational rights of asylum-seeking children and how international conventions have neglected these rights. To contextualize the ambiguity of asylum and education, the paper presents a case study of Norway’s reception of asylum-seeking children from the 1930s to the present day and how the Norwegian welfare system, which was founded on child rights protection, has struggled with the entry of unaccompanied asylum-seeking children. The paper concludes with reflections on the potential impact of education for these children, considering their encounters as temporary educational moments. This exploration focuses on clarifying historical strands, turning points, and threads rather than taking a subjective historical perspective.